1983
DOI: 10.1055/s-2007-1018667
|View full text |Cite
|
Sign up to set email alerts
|

Renal Impairment in Experimental Hemochromatosis in Rats

Abstract: Parenteral administration of iron as the complex with nitrilotriacetate resulted in moderate iron deposition in the renal cortex along with heavy deposition of iron in liver, heart, and exocrine pancreas. Iron treated rats exhibited slight but significant changes in serum chemistries consistent with mild renal insufficiency: increased chloride and creatinine and decreased sodium, calcium and CO2 content as a group with isolated increases in urea nitrogen (2/9) and phosphorus (3/9). Serum albumin was decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Cell‐free plasma hemoglobin can lead to progressive tubulointerstitial inflammation with upregulation of monocyte chemoattractant protein‐1 and nuclear factor‐κB and upregulation of both interstitial and basement membrane extracellular matrix components. In addition, hemosiderosis in the kidney with direct generation of free radicals has also been suggested as a mechanism for both acute and chronic kidney inflammation and fibrosis in PNH [14, 37]. Hemosiderosis was found in 9 of 10 patients in a recent MRI study of patients with PNH [16].…”
Section: Discussionmentioning
confidence: 99%
“…Cell‐free plasma hemoglobin can lead to progressive tubulointerstitial inflammation with upregulation of monocyte chemoattractant protein‐1 and nuclear factor‐κB and upregulation of both interstitial and basement membrane extracellular matrix components. In addition, hemosiderosis in the kidney with direct generation of free radicals has also been suggested as a mechanism for both acute and chronic kidney inflammation and fibrosis in PNH [14, 37]. Hemosiderosis was found in 9 of 10 patients in a recent MRI study of patients with PNH [16].…”
Section: Discussionmentioning
confidence: 99%
“…[192021] In animal models of experimental hemosiderosis, a decreased glomerular filtration rate (GFR) associated with tubular dysfunction is almost always present. [22] Not many patients of Fanconi syndrome due to PNH have been reported in the past. [21] In a previous report, a 51-year-old female had PNH diagnosed 17 years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term study, micro-infarctions due to repeated episodes of microvascular thrombosis were proposed as the major contributing factors in the development of chronic renal failure [14,15]. However, some authors suggested a direct nephrotoxic effect of iron, which can promote hydroxyl radical-mediated lipid peroxidation, leading to cell death [16]. Renal ultrasound findings are atypical and will only demonstrate morphological and Doppler changes due to chronic renal parenchymatous disease.…”
Section: Discussionmentioning
confidence: 99%